Tren Donasi Digital Bagi Gen ‘Z’ Mahasiswa Bali - Putri, Penny Kurnia (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 1 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
ABSTRACT Digital donation activities have become popular recently due to the Covid-19 pandemic. Billions of rupiah have been collected from millions of “good people” who are willing to set aside their income to help others. The use of technology is the main factor for this social action to achieve success. Students as representatives of Gen 'Z' in Society 5.0 should be considered for their existence when referring to Sustainable Development Goals (SDG’s). This research aims to determine the social entrepreneurship potential of students in Bali through their participation in the digital donation trend. Student participation in donating or initiating donation activities can be the basis for mapping the prospects for government programs related to entrepreneurship. The objective is to identify the social activists who can be relied on for sustainable development. The analysis was conducted qualitatively based on data from a combination questionnaire, group discussions and interviews. The results of this research indicate that the majority of Balinese students (84%) have become social capital assets. In the mapping of student behavior, researchers identified about 25 percent who are able to seize opportunities to develop social entrepreneurship, therefore they are called Active Agents. While the rest (later referred as Passive Agents), the majority have internal constraints, such as low self-confidence. Therefore, the researchers compiled several recommendations that could be considered by the institution to generate the social entrepreneurship potential in a sustainable manner.   ABSTRAK Aktivitas donasi digital menjadi populer baru-baru ini karena pandemi Covid-19. Miliaran rupiah sudah berhasil dikumpulkan dari jutaan “orang baik” yang mau menyisihkan penghasilannya untuk membantu sesama. Pemanfaatan teknologi menjadi faktor utama aksi sosial ini meraih kesuksesan. Mahasiswa sebagai representasi Gen ‘Z’ dalam Society 5.0 patut dipertimbangkan eksistensinya ketika merujuk pada tujuan pembangunan berkelanjutan. Penelitian ini bertujuan untuk mengetahui potensi kewirausahaan sosial mahasiswa di Bali melalui partisipasinya dalam tren donasi digital. Partisipasi mahasiswa untuk berdonasi maupun menginisiasi aktivitas donasi dapat menjadi landasan pemetaan prospek program pemerintah terkait kewirausahaan. Tujuannya jelas untuk mengidentifikasi sejak dini bibit pelaku usaha yang dapat diandalkan untuk pembangunan berkelanjutan. Analisis dilakukan secara kualitatif berdasarkan data dari kuesioner kombinasi, diskusi kelompok dan wawancara. Hasil penelitian ini menunjukkan bahwa mayoritas mahasiswa Bali (84%) telah menjadi aset kapital sosial. Pemetaan perilaku mahasiswa tersebut, diidentifikasi peneliti sekira 25 persen yang mampu meraih peluang untuk mengembangkan kewirausahaan sosial, oleh karenanya disebut Agen Aktif. Sedangkan sisanya (kemudian disebut sebagai Agen Pasif), mayoritas memiliki kendala internal, seperti faktor kepercayaan diri yang rendah. Maka dari itu, peneliti menyusun beberapa rekomendasi yang dapat menjadi bahan pertimbangan institusi untuk membangkitkan dan membina potensi kewirausahaan sosial mahasiswa secara berkelanjutan.